Immune-endocrine mechanisms in the link between stress and health. (September 2021) - Miller, Greg
Abstract : Children who are exposed to economic adversity in the early years of life show increased susceptibility to chronic diseases of aging, like heart disease, when they reach their 50's and 60's. These findings raise challenging but fascinating mechanistic questions: How does early adversity "get under the skin" in a manner that is sufficiently persistent to affect vulnerability to diseases that arise many decades later? Why are some children vulnerable to these risks, whereas others are protected? In this lecture I will discuss three emerging themes from our ongoing research. First, this work suggests that early adversity gets embedded in cells of the innate immune system at the level of the genome, resulting in a pro-inflammatory phenotype that probably contributes to the chronic diseases of aging. Second, we are seeing evidence that this phenotype arises as a result of excessive crosstalk between the innate immune system and brain circuitries involved in threat and reward processing. Finally, research on moderators has revealed powerful buffering effects of nurturant parenting, which offsets many of the risks associated with early adversity.